Amygdalin as a chemoprotective agent in co-treatment with cisplatin - Christodoulou, Panayiota; Boutsikos, Panagiotis; Neophytou, Christiana M.; Kyriakou, Theodora-Christina; Christodoulou, Maria-Ioanna; Papageorgis, Panagiotis; Stephanou, Anastasis; Patrikios, Ioannis (Frontiers in Pharmacology, 2022)
Amygdalin is a naturally occurring glycoside used in traditional Chinese medicine and is known to have anti-cancer properties. Even though the anti-cancer properties of Amygdalin are well known, its effect on normal cells has not been thoroughly investigated. The aim of the present study was to investigate a possible chemo-protective role of Αmygdalin against the cytotoxic effects of chemotherapy for normal human cells. Specifically, it was tested in combination with a strong chemotherapeutic drug Cisplatin. Human non-tumorigenic MCF12F epithelial cell line, human fibroblasts cells, human breast cancer MCF7 and MDA-MB-231 cells were treated with Cisplatin in a dose- and time-depended manner in the absence or presence of Amygdalin. When MCF12F cells and fibroblasts underwent pre-treatment with Amygdalin followed by Cisplatin treatment (24 hrs Amygdalin + 24 hrs Cisplatin), the cell viability was increased (22%, p < 0.001) as indicated using MTT assay. As attested by flow cytometry, combination treatment was associated with decreased the percentage of late apoptotic cells compared with monotherapy (fold-change of decrease=1.6 and 4.5 for 15μΜ and 20μΜ, respectively). Moreover, the levels of pro-apoptotic genes PUMA, p53 and BAX mRNA were significantly downregulated (~83%, ~66% and ~44%, respectively) vs Cisplatin alone, while the mRNA levels of anti-apoptotic genes BCl-2 and Bcl-XL were upregulated (~44.5% and ~51%, respectively), vs Cisplatin alone after 24h of combination treatment. The study on the Combination index (CI) assay indicated that Amygdalin could be possibly considered as an antagonist to Cisplatin (2.2 and 2.3) for MCF12F and fibroblast cells respectively. In contrast, for the breast cancer MCF7 and MDA-MB-231 cells, Amygdalin and Cisplatin indicated a synergistic effect (0.8 and 0.65), respectively. Our present findings suggest that when Amygdalin is used in combination with Cisplatin, can protect the normal breast cells as well as the fibroblasts during chemotherapy treatment, indicating a strong selective chemoprotective ability and may contribute to a better quality of life for cancer patients.